Komparasi Return dan Risiko Saham Syariah dan Konvensional Pada JII dan IDX30 Periode 2019-2023 - Marlinda, Marlinda; Syahputra, Hendra (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2024)
The purpose of this study is to compare the average return and risk of Islamic stocks and conventional stocks on the JII and IDX30. Data was taken from the IDX website which provides data on companies listed on the JII and IDX for the 2019-2023 period and Yahoo Finance which provides monthly stock closing price data on the JII and IDX during the 2019-2023 period. The sampling technique used purposive sampling method so that 3 sharia stocks and 5 conventional stocks were obtained. Data analysis uses descriptive and inferential statistics using a t-test to draw conclusions. The results of the Independent Sample T Test showed that the return variable obtained a significance value of 0.777>0.05 and the risk variable obtained a significance value of 0.209>0.05. So it is concluded that Islamic stocks and conventional stocks do not show significantly different levels of return and risk.